Menstrual health in figure skaters - Ackerman, K. (The Professional Skater PS Magazine, 2015)
In the United States, the median age of menarche (first menstrual period), is 12.5 years of age... Ninety-eight percent of all U.S. girls reach menarche by age 15. However, many athletes in lean sports (e.g. figure skating, ballet, gymnastics, running sports) first experience periods later than this. While it may be considered the "norm" to some athletes and coaches, it is important to realize that it is suboptimal and should be concerning.